Endoscopic laser endomicroscopy and “leaky gut” in patients with functional gastrointestinal symptoms and food intolerance - Frieling, Thomas; Gjini, Besmir; Melchior, Ilka; Euler, Philipp; Kreysel, Christian; Kalde, Sigrid; Krummen, Britta; Kiesslich, Ralf; Hemmerlein, Bernhard (Zeitschrift für Gastroenterologie, 2022)
Background Intestinal epithelial barrier dysfunction (“leaky gut syndrome”, LGS) is thought to play a major role in the pathogenesis of disorders of the gut brain axis. Endoscopic confocal laser endomicroscopy (eCLE) is an objective measure to test duodenal permeability. We applied this technique in patients with functional gastrointestinal symptoms and food intolerance to characterize the proportion of patients with LGS.Material and Methods In an observational study, we evaluated 85 patients with functional gastrointestinal symptoms and food intolerance. Gastrointestinal symptoms were classified according to Rom IV into functional abdominal pain (FAP), irritable bowel syndrome (IBS), irritable bowel syndrome diarrhea dominant (IBS-D), irritable bowel syndrome constipation dominant (IBS-C), irritable bowel syndrome with mixed stool (IBS-M), functional abdominal bloating (FAB), functional diarrhea (FD) and unclassified (NC). During eCLE, spontaneous transfer of intravenously applied fluorescein into duodenal lumen (LGS) and following duodenal food challenge (DFC) were analyzed. Blood analysis comprised parameters of mast cell function, histology of duodenal mucosal biopsies analysis of mucosal inflammation, intraepithelial lymphocytes (IELs) as well as number, distribution and morphology of mast cells.Results 24 patients (9 IBS, 9 FAP, 3 FAB, 1 FD, 2 NC), showed LGS, 50 patients (14 IBS-D, 4 IBS-C, 3 IBS-M, 23 FAP, 3 FAB, 3 NC) had no LGS but responded to DFC and 11 patients (6 NC, 3 FAP, 1 FAB, 1 FD) had no LGS and no response to DFC. The proportion of subgroups with/or without spontaneous leakage of fluorescein (+LGS/-LGS) were IBS-LGS/IBS+LGS 67%/33%, FAP-LGS/FAP+LGS 72%/28%,FAB-LGS/FAB+LGS 50%/50%, NC-LGS/NC+LGS 60%/40%. Subgroup analysis revealed no significant differences for all parameters tested.Conclusion As a proof of concept, the results of our study indicate that eCLE is a clinical useful tool to evaluate patients with disorders of the gut brain axis and those suspicious of LGS. However, the clinical significance of LGS remains unclear. The study should be an incentive to perform a randomized study including healthy controls.
Keywords: Endoscopic laser endomicroscopy (eCLE); “leaky gut syndrome”; functional gastrointestinal symptoms; irritable bowel syndrome (IBS); disorders of the gut-brain-axis; food intolerance